2019
DOI: 10.1111/vru.12757
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular injection of a Tin‐117 m radiosynoviorthesis agent in normal canine elbows causes no adverse effects

Abstract: This longitudinal prospective exploratory study used serial measurements in five dogs to evaluate safety and retention of a tin-117 m ( 117m Sn) colloid after intra-articular injection in normal elbow joints. Each dog was deemed healthy based on physical examination, laboratory results, and radiographic evaluation of both elbows. While anesthetized, each received an MRI of both elbows, followed by fluorine-18 fluorodeoxyglucose positron emission tomography scans of both elbow joints and associated lymph nodes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The absence of any adverse effects in the present study and in a previous experimental study, is most likely due to unique characteristics of 117m Sn. 23 , 25 , 26 Tin 117m emits abundant conversion electrons, low-energy particles with a short, non-diminishing penetration range of approximately 300μm in tissue. Other radionuclides that emit beta particles result in variable tissue penetration and can result in damaging irradiation of adjacent non-target tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The absence of any adverse effects in the present study and in a previous experimental study, is most likely due to unique characteristics of 117m Sn. 23 , 25 , 26 Tin 117m emits abundant conversion electrons, low-energy particles with a short, non-diminishing penetration range of approximately 300μm in tissue. Other radionuclides that emit beta particles result in variable tissue penetration and can result in damaging irradiation of adjacent non-target tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 24–26 In a recent prospective safety study of 5 dogs, blood, urine, feces, and organ scintigraphy counts showed that >99% of 117m Sn activity was retained in the elbow joint for approximately 6–7 weeks. 23 There were no adverse effects, and post-mortem evaluation revealed no joint damage. These findings, combined with the potential for protracted clinical improvement after a single IA injection, justify further evaluation of 117m Sn for the management of canine OA.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations